Model solving of aluminium alloy solidification - Jarosova, Tereza; Skocilasova, Blanka; Klimenda, Frantisek; Sterba, Jan; Cernohlavek, Vit (Manufacturing Technology Journal, 2021)
The paper deals with the process of solidification of a cast aluminium piston into a metal mould (mould). The introductory part presents the methodology of solution where the physical properties of both the aluminium alloy and the steel mould are presented. Furthermore, the solution itself is described, which is performed on one quarter the size of a piston model by using FEM in the ANSYS FLUENT program. Piston solidification temperatures were recorded every five minutes due to the solution complexity. Next part of the paper pre-sents the evaluation where temperature sections in two mutually perpendicular planes and a quarter a size 3D model of piston solidification are presented. At the end of the paper, an overall evaluation of the thermal so-lidification of the cast piston depending on the solidification time is performed. The results of the numerical solution show that the solidification process begins at 2.5 minutes after casting and ends at 5 minutes. Subse-quently, only the piston and the metal mould itself are cooled.
Keywords: crystallization; aluminium alloy; mould; gravity casting; FEM